PERAN DIGITAL LITERACY DALAM MEMODERASI PENGARUH PERCEIVED DESIRABILITY DAN PERCEIVED FEASIBILITY TERHADAP MINAT BERWIRAUSAHA GENERASI Z DI KECAMATAN PETANG PADA ERA DIGITAL - Aghivirwiati, Gusti Ayu; Triana Arisanti, Ni Komang; Rindi Antika, Ni Kadek (Buletin Studi Ekonomi; VOLUME.29.NO.02.TAHUN.2024DO - 10.24843/BSE.2024.v29.i02.p09, 2024)
Entrepreneurial intention research includes theories that focus on predicting entrepreneurial behavior, such as the Theory of Entrepreneurial Events and the Theory of Planned Behavior. For example, perceived desirability and perceived feasibility are factors that influence entrepreneurial intentions. In this research, digital literacy is considered as a moderating factor that influences entrepreneurial intentions. Digital literacy involves different types of literacy and involves the ability to process information, communicate effectively, and use technology appropriately. This research seeks to fill the knowledge gaps that exist in the literature on entrepreneurship by adding the moderating factor of digital literacy. It is hoped that the results of this research will provide a deeper understanding of how factors such as perceived desirability, perceived feasibility, and digital literacy influence entrepreneurial intentions in the Generation Z context.